High Expression of FAP in Colorectal Cancer Is Associated With Angiogenesis and Immunoregulation Processes - Coto-Llerena, Mairene; Ercan, Caner; Kancherla, Venkatesh; Taha-Mehlitz, Stephanie; Eppenberger-Castori, Serenella; Soysal, Savas D.; Ng, Charlotte K. Y.; Bolli, Martin; von Flüe, Markus; Nicolas, Guillaume P.; Terracciano, Luigi M.; Fani, Melpomeni; et al. (Frontiers in Oncology, 2020)
Fibroblast activation protein α (FAP) plays an important role in tissue remodeling and helps tumor cells invade surrounding tissue. We sought to investigate FAP as a prognostic molecular marker in colorectal cancer (CRC) using immunohistochemical and transcriptomic data. FAP expression and clinicopathologic information were obtained from The Cancer Genome Atlas dataset. FAP association with tissue cellular heterogeneity landscape was explored using xCell method. FAP protein expression was evaluated in a cohort of 92 CRCs and 19 non-tumoral tissue. FAP was found upregulated in tumors both at the mRNA and protein levels and its expression was associated with advanced stages, poor survival and consensus molecular subtype 4. FAP expression was associated with angiogenesis and collagen-degradation. We observed an enrichment in immune-cell process-related genes associated with FAP overexpression. CRCs with high-FAP expression display an inflamed phenotype enriched for macrophages and monocytes. Those tumors showed enrichment for Treg populations and depletion of Th1 and natural killer T cells, pointing to an immunosuppressive environment. CRCs with high levels of stromal FAP are associated with aggressive disease progression and survival. Our results suggest other roles of FAP in tumor progression such as modulation of angiogenesis and immunoregulation in the tumor microenvironment.